Positive Psychological Capital (PsyCap) (Conceptual Perspective in Core Basics and Requirements for building and Preparing) - حمود, سعد علي; ابراهيم, ابراهيم خليل (Journal of Economics and Administrative Sciences, 2012)
This research aim to exploring the positive psychological capital concept (PsyCap) which drawn from positive psychology and applying it at workplace. PsyCap emerged as extending for recent another types of capital, such as human capital and social capital. It has been defined as “an individual’s positive psychological state of development". The PsyCap consist of four core constructs (self- efficacy, optimism, hope, and resilience). Each of the four components has considerable theorizing and researching that can contribute to developing an integrative theoretical foundation for PsyCap. But their combined motivational effects will be broader and more impactful than any one of the constructs individually. The research relies on  a comprehensive review of literature through  studying and analyzing related references, and then drawing a number of conclusions and practical recommendations in order to considered as a motivation path for our organizations and leaders to adopting this subject and concerning it as a part of their cultures.